Determination of Anticancer and Antimicrobial Properties of Alcea calvertii - Keser, Serhat; Tekin, Suat; Kaygili, Omer; Keser, Fatma; Turkoglu, Ismail; Turkoglu, Semra; Sandal, Suleyman (Wiley-Blackwell, 2016)
[Abstract Not Available]